Analysis of Sovereign Yield Spreads Behavior: The French Bonds Case - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The introduction of the Euro has led to price level stability and fostered growth within the European Union. Consequently, since its launch as a store of value and unit of account, there has been a clear convergence between the yield of France's sovereign debt and German benchmark. This paper tries to estimate the effect of certain macroeconomic fundamentals on the yield spread of French 10-year bonds, relative to the German Bund of the same maturity for the period January 1999-March 2003. It reaches the conclusion that staying in line with Maastricht criteria decreases the risk premium of external debt.
Keywords: G12; G15; 330; French bonds; yield spreads